2018
DOI: 10.1002/uog.18813
|View full text |Cite
|
Sign up to set email alerts
|

International Endometrial Tumor Analysis (IETA) terminology in women with postmenopausal bleeding and sonographic endometrial thickness ≥ 4.5 mm: agreement and reliability study

Abstract: Inter- and intrarater agreement and reliability when using IETA terminology were limited. This may have implications when assessing the association between a particular ultrasound feature and a specific histological diagnosis, because lack of reproducibility reduces the reliability of the association between a feature and the outcome. Future studies should investigate whether using fewer categories of variable or offering practical training could improve agreement and reliability. Copyright © 2017 ISUOG. Publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 41 publications
(53 reference statements)
0
16
0
Order By: Relevance
“…Furthermore, the most relevant study on endometrial thickness measured transvaginal, which included 48,230 postmenopausal women [35], revealed that a cut-off of >5.15 mm is relevant for endometrial hyperplasia and cancer. Due to differences generated by practitioners in measuring and interpretation of ultra-sonographic results [36], a consensual, unique working protocol for ambulatory gynecological assessment is required. IETA (International Endometrial Tumor Analysis group) proposed an algorithm, which includes, besides endometrial thickness, the endometrial volume that might be of help in differentiating benign from malignant endometrial lesions [5,37].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the most relevant study on endometrial thickness measured transvaginal, which included 48,230 postmenopausal women [35], revealed that a cut-off of >5.15 mm is relevant for endometrial hyperplasia and cancer. Due to differences generated by practitioners in measuring and interpretation of ultra-sonographic results [36], a consensual, unique working protocol for ambulatory gynecological assessment is required. IETA (International Endometrial Tumor Analysis group) proposed an algorithm, which includes, besides endometrial thickness, the endometrial volume that might be of help in differentiating benign from malignant endometrial lesions [5,37].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an additional attempt to identify women who may have endometrial hyperplasia, rather than a benign proliferative endometrium, on ultrasound would not have made a clinical difference to their initial management. Furthermore, by reducing the number of options available to the rater, we aimed to improve inter‐rater reliability, as proposed in a study by Sladkevicius et al 26 …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the inter-rater reliability of subjective ultrasound pattern recognition and its diagnostic accuracy may be poorer when performed by less-experienced operators [23][24][25] . Furthermore, the intraand inter-rater reliabilities when using IETA terminology to describe ultrasound images of the endometrium were also found to be poor 26 . Notwithstanding these potential limitations, others have suggested that we should invest more in ultrasound training and consider limiting our use of different terminologies to those that are most reproducible 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Sladkevicius and Valentin showed that the subjective assessment of benign and malignant tumors based on the work of the International Ovarian Tumor Analysis Group reached excellent reproducibility between 2 experienced raters. However, Leone et al concluded that there was limited agreement and reliability when using the terms of the International Endometrial Tumor Analysis Group and suggested that to improve the reproducibility, individual features should be combined, and training workshops should be available.…”
Section: Discussionmentioning
confidence: 99%